2014
DOI: 10.1007/s00439-014-1515-4
|View full text |Cite
|
Sign up to set email alerts
|

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk

Abstract: Several studies have reported associations between multiple cancer types and single-nucleotide polymorphisms (SNPs) on chromosome 5p15, which harbours TERT and CLPTM1L, but no such association has been reported with endometrial cancer. To evaluate the role of genetic variants at the TERT–CLPTM1L region in endometrial cancer risk, we carried out comprehensive fine-mapping analyses of genotyped and imputed SNPs using a custom Illumina iSelect array which includes dense SNP coverage of this region. We examined 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 60 publications
(84 reference statements)
2
31
0
Order By: Relevance
“…This SNP set was defined as the SNPs which were in LD (r 2 > 0.2) and had a likelihood of association with endometrial cancer < 100:1 with the relevant lead SNP (Carvajal-Carmona et al 2015; Glubb, et al 2015). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This SNP set was defined as the SNPs which were in LD (r 2 > 0.2) and had a likelihood of association with endometrial cancer < 100:1 with the relevant lead SNP (Carvajal-Carmona et al 2015; Glubb, et al 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Lead SNP, rs79575945 is also reported to be associated with expression of SYNE1 , adjacent to ESR1 . Given SNPs at this locus have previously been identified as predisposing to breast cancer, also a hormonally driven cancer, this study adds weight to the rationale for performing informed candidate fine-scale genetic studies across cancer types (Carvajal-Carmona et al 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent CGA analysis demonstrated high expression levels of TERT and cleft lip and palate transmembrane protein 1-like protein in endometrial cancer (67). TERT is highly expressed in DNA copy number-stable cancers, including thyroid carcinoma (68), and in endometrial cancer with a low genome copy number (69).…”
Section: Genomic Analysis In Endometrial Cancermentioning
confidence: 99%
“…Up till now, fine mapping studies have identified multiple independent cancer susceptibility loci in TERT-CLPTM1L region for a specific cancer type, such as breast, ovarian, and prostate cancer. [16][17][18][19] Much more efforts were also performed in lung cancer, and several novel genetic variants were identified as lung cancer risk loci. 18,20,21 In 2013, Walsh et al 9 conducted a fine mapping study in 5p15.…”
mentioning
confidence: 99%